The Effect of Financial Performance and Company Size on Company Value: A Review of Literature Studies - Abdulrival Hartoyo; Darman; Amnatia R Abdullah (Eastasouth Institute, 2023)
The literature review article on the Effect of Financial Performance and Company Size on Company Value aims to formulate a research hypothesis that evaluates the relationship between these variables in future research. The method for writing this literature review article is based on the literature review research method, with data sources coming from various platforms such as Google Scholar, Mendeley, Semantic Scholar, and other online academic sources. The findings from this literature review article show that financial performance has a significant impact on company value, while company size has no effect on company value.